Fish and ram. Banqueting with the Danubian Rider Gods - Nemeti, Sorín; Nemeti, Irina (ARYS. Antigüedad: Religiones y Sociedades, 2020)
The present study analyzes the cult of the so-called Danubian Riders, with special emphasis on the sacrifices and sacred food involved. As primary sources the study uses the three-row reliefs that were made and circulated in the province of Dacia, and other variants of the lead tablets that were mostly distributed in Pannonia Inferior, around the center of Sirmium. These selected monuments reveal themselves as developed forms of this cult’s iconography, narrating mythical episodes through symbolic scenes and describing ritual acts. These complex iconographies are pseudonarrative because they include, among the diachronically ordered key scenes, essential data on the cult, the exponential moments of both the mythical and ritual rows. The meat of both fish and ram becomes the sacred food of the Gods and of the people adoring them, around a complex myth and ritual.